Identificación de las principales plagas del cultivo del maíz suave (Zea mays L.) en la parroquia de Eugenio Espejo, Otavalo, Imbabura - Isama Amaguaña, Alberto (2019)
SUMMARY The present work of investigation in the traditional culture of the maize, describes with the end to identify, characterize and evaluate the main plagues and the illnesses in the traditional crop of the corn (Zea mays L.). The cultivation of corn is based mainly on the pests and diseases that affect its production; Subsequently, several visits were made to the crops with which they were published to corn farmers, to then conduct surveys to 10 farmers, taking into account that it is the vast majority of them are engaged in this crop traditionally. Within the surveys, the following points are mainly evaluated, with respect to the cultivation of corn in the Eugenio Espejo zone: cultivation area, classification of seeds, planting varieties, type of planting, crop management and, above all, the main pests that coincide and its incidence in the traditional cultivation of corn, are also observed with details on the causes and problems that affect the producers of the area in the production of corn. Keywords: Identify pests, corn